The role of epigenic mechanisms in the adaptive evolution - Stajic, Dragan (2021)
"Natural selection acts upon the variation in fitness-related traits within a population. Inheritance of this variation is of paramount importance for this process. Evolution of any inherited trait related to reproductive success will proceed, regardless of its molecular mechanism of inheritance. Mendel´s discoveries and definition of the particulate form of inheritance alongside the discovery that the instructions for phenotypic traits are encoded in the nucleotide sequence within DNA strand lead to the formalization of the Modern Synthesis.(...)"